marked as licensing oil and its role in future oil industry in Iraq - الراوي, احمد عمر (Journal of Economics and Administrative Sciences, 2011)
Iraq's oil industry  has been passed  in different periods , began with domination  of  Western companies to invest in Iraqi oil at twenties of the last century ,  through the process of nationalization of the shares of those companies ,  beginning of the seventies , and ending with the new policies adopted by the government recently, which was contracting with international companies to develop the oil industry , because of what the outcome of the oil industry from a decline in artistic and  physical ability as a result to the  conditions of war and embargo imposed on Iraq before 2003.The Iraqi government has introduced licensing of a contract to develop oil fields produced through two rounds of competition involving a number of companies and global conglomerates to enter long-term contracts to develop oil fields in return for wages for every specific product onto a barrel. It  has been contracted with a number of companies that won contracts to develop oil fields like ( Majnoon  ,  Al-Halfiyah  ,  West Al- Qurnah ,  Al-Gharraf and Badrah )  , it is expected to boost the implementation of these contracts, production capacity from the current rates, estimated at 2 million barrels / day to about 12 million barrels per day of crude oil beginning of the second decade of this century .Such contracts have raised heated debate between supporters and opponents arguing that its contracts referred to lack legal basis and return it to the control of overseas companies on Iraq's oil wealt